Factors Influencing the Popularity of a Health-Related Answer on a Chinese Question-and-Answer Website: Case Study - Li, Jinhui; Zheng, Han; Duan, Xu (Journal of medical Internet research, 2021)
Background: Social question-and-answer (Q&A) sites have become an important venue for individuals to obtain and share human papillomavirus (HPV) vaccine knowledge. Objective: This study aims to examine how different features of an HPV vaccine–related answer are associated with users’ response behaviors on social Q&A websites. Methods: A total of 2953 answers and 270 corresponding questions regarding the HPV vaccine were collected from a leading Chinese social Q&A platform, Zhihu. Three types of key features, including content, context, and contributor, were extracted and coded. Negative binomial regression models were used to examine their impact on the vote and comment count of an HPV vaccine–related answer. Results: The findings showed that both content length and vividness were positively related to the response behaviors of HPV vaccine–related answers. In addition, compared with answers under the question theme benefits and risks, answers under the question theme vaccination experience received fewer votes and answers under the theme news opinions received more votes but fewer comments. The effects of characteristics of contributors were also supported, suggesting that answers from a male contributor with more followers and no professional identity would attract more votes and comments from community members. The significant interaction effect between content and context features further showed that long and vivid answers about HPV vaccination experience were more likely to receive votes and comments of users than those about benefits and risks. Conclusions: The study provides a complete picture of the underlying mechanism behind response behaviors of users toward HPV vaccine–related answers on social Q&A websites. The results help health community organizers develop better strategies for building and maintaining a vibrant web-based community for communicating HPV vaccine knowledge.